The Phenomenon of Space Commercialization: is it in Contrast to the Province of All Mankind Principle? - Arnanda Yusliwidaka; Frista Arisa; Jaduk Gilang Pembayun; Satrio Ageng Rihardi; Muhammad Ardhi Razaq Abqa (Universitas Trunodjoyo Madura, 2026)
Space is a region under international jurisdiction. No single country or other subject of international law is permitted to claim ownership of space. This is due to the establishment of one of the main principles in space law, i.e. the province of all mankind principle. This principle emphasizes that space belongs to all mankind and must be fully utilized for the benefit of humanity. The phenomenon of commercialization in space having occurred in modern era is the impact of the rapid progress of science and technology. Commercialization in space is an activity to utilize the region, and then to gain economic benefits. Not only countries but also the private sector with high technology and large resources has participated in the implementation of space commercialization. The forms commercialization of space include, among others, space tourism, telecommunications, insurance, and others. This phenomenon has been debated until today, considering that space belongs to all mankind and must be fully utilized for the benefit of humanity. However, in reality, what happens is that this region is managed by several developed countries and private sector for their economic interests. This study aims to comprehensively analyze commercialization in outer space from the perspective of the province of all mankind principle, one of the main principles in space law. This analysis aims to provide certainty concerning the implementation of commercialization and ensure fairness in the utilization of outer space.